The Right of Anthroposophic Medicine: - Zuck, Rüdiger (Nomos Verlagsgesellschaft mbH & Co. KG, 2012)
The second edition of The Right of Anthroposophic Medicine aims to give consideration to the unabated interest shown by patients in the specific therapeutic approaches which diverge from orthodox medicine. The independent approach of anthroposophic medicine is based on the image of the human being developed by Rudolf Steiner. This image is spelled out in the “Declaration on the rights of anthroposophic medicine” drawn up in 2011 by the Medical Section of the School of Spiritual Science at the Goetheanum in Dornach joined by a legal commentary. The fundamental aim of the present study is to describe the situation in law pertaining to anthroposophic medicine while at the same time setting out its claim to be practiced as a special therapeutic approach. Anthroposophic medicine proceeds on the basis that the understanding of natural science about the structure and functioning of the human body is extended by three components in addition to the physical body, namely the etheric body, the astral body and the I-organisation. In this context the publication aims to highlight the dual function contained in the German term “Recht” which comprises both the meaning of “law” and of “rights”. It thus describes both the current state of law as well as a claim to rights which arises not just from current law but also serves to fix what anthroposophic medicine wishes to see as being assured with regard to its own autonomy.The author, an expert in constitutional law, looks at anthroposophic medicine from the outside. His legal considerations are based solely on a pluralistic approach which endeavours to support and promote a diversity of possible opinions.